2021
DOI: 10.1039/d1nj00051a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence ‘off–on–off’ signaling with zinc ensemble: a new array of investigating prevalence of ATP in liver cancer cells

Abstract: 2-Hydroxy naphthaldehyde–picolylamine conjugate (NPAC) ensemble with Zn2+ (NPAC–Zn2+) has been synthesized for the selective recognition and estimation of ATP in human liver cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Furthermore, when ATP was added to this 68-Zn 2+ complex, the fluorescence was quenched significantly (68-Zn 2+ -ATP) due to the better binding affinity of ATP towards Zn 2+ . 102 It was found that sensors with dual sensing properties are able to detect ATP ions followed by the complexation with…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when ATP was added to this 68-Zn 2+ complex, the fluorescence was quenched significantly (68-Zn 2+ -ATP) due to the better binding affinity of ATP towards Zn 2+ . 102 It was found that sensors with dual sensing properties are able to detect ATP ions followed by the complexation with…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…Furthermore, when ATP was added to this 68-Zn 2+ complex, the fluorescence was quenched significantly ( 68-Zn 2+ -ATP ) due to the better binding affinity of ATP towards Zn 2+ . 102 It was found that sensors with dual sensing properties are able to detect ATP ions followed by the complexation with certain metal ions. It was reported that the red emission of a carbon dots–quercetin (CDs-QCT) system exhibited a dual-sensing property towards Zn 2+ and ATP ions.…”
Section: Chemosensors For the Detection Of Atpmentioning
confidence: 99%
“…[48][49][50] It is found that several Zn complexes based on thiocarbazole, pyrene, and naphthaldehyde have ATP detection efficacy. 51,52 However, no report of a simple Schiff-base Zn(II) complex being used as an effective ATP sensor has been found (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…27 A higher or lower level of ATP causes symptoms such as hypoxia, hypoglycaemia, and Parkinson's disease, 28,29 whereas an elevated level of ATP is associated with various malignant tumors. 30 Several analytical methods, such as electrochemistry, 31 electrochemiluminescence, 32 surface-enhanced Raman scattering, 33 colorimetry, 34,35 and fluorimetry, [36][37][38] have been developed for ATP recognition. [39][40][41][42] Most of these ATP biosensors relied on the use of a specific aptamer, which can scarcely discriminate ATP from adenosine monophosphate (AMP).…”
Section: Introductionmentioning
confidence: 99%